IMPACT OF QUALITY OF LIFE IN FRONT OF URINARY INCONTINENCE IN OLDER PEOPLE'S (Fiep Bulletin - online, 2016)
Introduction: Although aging is physiological, is seen by society more vulnerable to disease and may interfere with the autonomy, mobility, manual dexterity, lucidity and functional capacity of the bladder and lower urinary tract, favoring the emergence of Urinary Incontinence (IU). The UI is present in the whole population, it is the complaint of any involuntary leakage of urine, negatively affecting the quality of life of incontinent people.Objective: To determine the prevalence of UI in the elderly of both sexes, to assess the impact of quality of life in front of urinary incontinence and the moment of loss prevalent in this population.Methods: 50 elderly people above 60 years of age were interviewed, a center that serves the community of Cascavel - PR. The volunteers answered a questionnaire, called International Consultation on Incontinence Questionnaire - Urinary Incontinence / Short Form (ICIQ / SF), adapted to the Portuguese applied in May and June 2014. For statistical analysis, the data were tabulated in Microsoft Office Excel 2010 and later analyzed by the researcher.Results: 44% of our volunteers do not show loss of urine and 56% of individuals have some type of urinary incontinence, with 35.7% male and 64.3% female. As for the impact of quality of life in incontinent individuals, 46% reported very severe impact. Regarding the moment of urine loss, lose 22% just before reaching the toilet and 16% lose when they cough or sneeze.Conclusion: The study revealed a high prevalence of urinary incontinence in elderly women. Much of incontinent individuals reported having a serious impact on their quality of life. And as regards the timing of urine loss, the most cited by volunteers were lost just before reaching the toilet.
Keywords: Urinary Incontinence; Aged; quality of Life.